The profile of imagining - Hopkins, Robert (Oxford University Press, 2024)
Imagining is a central power of the mind. When we visualise how something looks, or imagine how some combination of ingredients might taste, we picture absent things in a way that captures what it would be like to experience them. This book offers an original theory of the nature of this important mental phenomenon and its role is in our lives
Keywords: Imagination; Philosophy of Mind; Repräsentation -- Philosophie; Visuelle Vorstellung; Image (Philosophy); Visualization / Philosophy; Image (Philosophie); Visualisation / Philosophie